Contributions to the washboard effect evaluation on unpaved roads (2025)
Washboard or corrugation is a common phenomenon on unpaved roads, characterized by undulating patterns that not only cause discomfort to drivers but also pose safety risks due to the loss of wheel-road contact. This study integrates experimental, theoretical, and real-scale measurement approaches to provide some understanding of the washboard phenomenon. Experimentally, the research evaluated key physical variables controlling washboard development using a multi-pass system in which a rotating wheel traverses a sandy path. Variables such as wheel velocity, wheel mass, and soil properties were examined to assess their influence on undulation formation. Theoretically, a model was developed to compute soil permanent displacements and contact forces by incorporating a simple rheological model, dynamic equilibrium principles, soil-bearing capacity, and macro-element models based on a conical stress distribution. Additionally, the washboard phenomenon was analyzed through particle transport dynamics, by applying a theoretical model previously proposed for sand dune formation. This approach evaluates ripple development via saltation and creep processes under variable wheel velocities and soil densities. Furthermore, the study examines the effectiveness of geosynthetic reinforcement at the road surface by evaluating a cellular confinement system (geocells). The use of geocells was found to enhance soil shear resistance and reduce undulation formation, as demonstrated by comparative experiments on reinforced and non-reinforced tracks. Finally, real-scale measurements from four Ecuadorian unpaved roads were analyzed to assess vehicle behavior at varying speeds. Overall, the findings provide some insights into the driving mechanisms of washboard development and show that vehicle velocity is a critical factor. Additionally, a feasible mitigation strategy is proposed, which may contribute to improved road performance and safety.